A numerical investigation into the influence of bio-inspired leading-edge tubercles on the hydrodynamic performance of a benchmark ducted propeller. (1st October 2021) - Stark, Callum; Shi, Weichao; Atlar, Mehmet
Abstract: Marine ducted thrusters are widely used to provide propulsive thrust for a range of marine vessels due to their high thrust capability in heavy loaded conditions. This paper presents a novel and optimised bio-inspired marine ducted thruster, where leading-edge tubercles are applied to the duct of a ducted propulsor to explore the impact on hydrodynamic performance. Nine different geometrical configurations of tubercle were investigated with varying amplitude and wavelength within the optimisation study. The hydrodynamic performance of the marine ducted thruster is evaluated using a commercially available computational fluid dynamics (CFD) code, STAR-CCM+, with an incompressible implicit unsteady Reynolds-Averaged Navier Stokes (RANS) solver combined with the Body Force Propeller (BFP) method for the duct optimisation study. Then, the selected optimal duct was chosen for further analysis using the propeller resolved Rigid Body Motion (RBM) method, more commonly known as the sliding mesh technique. Through the numerical optimisation study, the leading-edge modification is predicted to have the capability to enhance the duct thrust in the heavy-loaded conditions, although this is dependent on the wavelength and amplitude of the tubercle. Furthermore, during the investigation the traditional tubercle behaviour was observed, namely the high-low pressure patterns and streamwise counter-rotating vortices. Interestingly, flow separation was observed to be compartmentalised on the outer side of the duct cross-section in conditions where flow separation occurred such as at the maximum efficiency operating point. Highlights: Leading-edge tubercles are applied to a duct of a benchmark ducted propeller and hydrodynamic performance is investigated. A design optimisation process was conducted, showing that the geometrical parameters of the tubercle vary the duct thrust. The traditional counter-rotating streamwise vortices and high-low pressure patterns were observed due to the tubercles. Flow separation compartmentalisation was observed on the outer duct section at the maximum efficiency operating point. It was shown that duct thrust capability and overall propulsive efficiency could be enhanced with leading-edge tubercles.